Geometrical parameter analysis of a high-sensitivity fiber optic angular displacement sensor - Sakamoto, Joao M. S.; Pacheco, Gefeson M.; Kitano, Claudio [UNESP]; Tittmann, Bernhard R. (Optical Soc Amer, 2014)
In this work, we present an analysis of the influence of geometrical parameters on the sensitivity and linear range of a fiber optic angular displacement sensor, through computational simulations and experiments. The geometrical parameters analyzed are the lens focal length, the gap between fibers, the fiber cladding radii, the emitting fiber critical angle (or, equivalently, the emitting fiber numerical aperture), and the standoff distance (distance between the lens and the reflective surface). Besides, we analyze the sensor sensitivity regarding any spurious linear displacement. The simulation and experimental results show that the parameters that play the most important roles are the emitting fiber core radius, the lens focal length, and the light coupling efficiency, whereas the remaining parameters have little influence on the sensor characteristics. (C) 2014 Optical Society of America